BmSd gene regulates the silkworm wing size by affecting the Hippo pathway. (21st July 2019) - Yin, Jin; Zhang, Jing; Li, Tao; Sun, Xia; Qin, Sheng; Hou, Cheng‐Xiang; Zhang, Guo‐Zheng; Li, Mu‐Wang
Abstract: Insect wings are developed from the wing disc during metamorphosis. Bombyx mori, a model lepidopteran insect, loses flight ability after long‐term domestication from the wild silkworm, Bombyx mandarina . The mw mutant (u11 strain) shows minute wings compared to wild type (e.g., p50 strain) wings. RNA sequencing analysis previously revealed differential Hippo‐pathway‐related gene expression between the u11 and p50 strains. The Hippo pathway is an evolutionarily conserved signaling cascade that controls organ size during development in animals. In this study, the function of BmSd which has been characterized as one of the Hippo‐pathway‐related genes was analyzed for silkworm wing development. We found that mats, warts, and hippo expression levels were higher in u11 compared to p50 wing discs. BmSd ( scalloped ) expression, which encodes a prominent transcriptional partner to Yorkie (Yki), gradually decreased during the wandering stage in u11, but exhibited the opposite expression pattern in p50. When BmSd was knocked down by small interfering RNA during the wandering stage in the p50 strain, 57.9% of the individuals showed minute wings. Additionally, ex, kibra, and wingless expression levels decreased in the BmSd knockdown mutant. Further, BmSd deletion mediated by clustered regularly interspaced short palindromic repeats (CRISPR) / CRISPR‐associated protein 9 induced 50% of individuals with minute wings, a phenotype similar to the mw mutant. This result demonstrates that BmSd plays pivotal roles in silkworm wing development. Our results show that the Hippo signaling pathway participates and plays crucial roles in the regulation of silkworm wing development, and our findings provide a basis for further research on B. mori wing development.